From Crisis to Convergence : Charting a Course for Portugal - Gershenson, Dmitry (Departmental Papers; Departmental Paper ;, 2016)
In 2011, following years of large-scale external imbalances financed by debt, Portugal's economy reached a crisis point. To restore economic growth and credibility with international lenders, the country embarked on a difficult path of fiscal adjustment and structural reforms. By many metrics, Portugal's 2011-14 macroeconomic stabilization program has been a success, but going forward Portugal would benefit from policies to reduce vulnerabilities, absorb labor slack, and generate sustainable growth.